Two new species of the genus Parareicheia Jeannel, 1957 (Coleoptera: Carabidae: Scaritinae: Clivinini: Reicheiina) from Portugal, with faunistic notes on Anillini - Serrano, Artur R.m.; Aguiar, Carlos A.s. (Zootaxa, 2026)
Two new microphtalmic beetle species of the genus Parareicheia Jeannel, 1957, from Portugal are described: Parareicheia renei sp. nov. and Parareicheia barrosi sp. nov. These endogean species are diagnosed and compared with closely related endemic species from the Iberian Peninsula. The external morphology and male genitalia of both new species, as well as the female genitalia of P. barrosi sp. nov., are illustrated, and information on species’ ecology is provided. A dichotomous key for the identification of Parareicheia species is also presented. New faunistic records of Geocharis moscatelus Serrano & Aguiar, 2001 and Geocharis submersus Serrano & Aguiar, 2003 are additionally reported.